Answer:
0
Step-by-step explanation:
0 · |-6|
Absolute value means take the non negative number
0* 6
0
Answer:
StartRoot 2 squared + 6 squared EndRoot
Step-by-step explanation:
we have
A(4,3) and B(-2,1)
we know that
the formula to calculate the distance between two points is equal to
![d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28y2-y1%29%5E%7B2%7D%2B%28x2-x1%29%5E%7B2%7D%7D)
substitute the given values
![AB=\sqrt{(1-3)^{2}+(-2-4)^{2}}](https://tex.z-dn.net/?f=AB%3D%5Csqrt%7B%281-3%29%5E%7B2%7D%2B%28-2-4%29%5E%7B2%7D%7D)
![AB=\sqrt{(-2)^{2}+(-6)^{2}}](https://tex.z-dn.net/?f=AB%3D%5Csqrt%7B%28-2%29%5E%7B2%7D%2B%28-6%29%5E%7B2%7D%7D)
![AB=\sqrt{40}\ units](https://tex.z-dn.net/?f=AB%3D%5Csqrt%7B40%7D%5C%20units)
therefore
StartRoot 2 squared + 6 squared EndRoot
Answer:
−6x+18
Step-by-step explanation:
-6(x-3)
(−6)(x+−3)
=(−6)(x)+(−6)(−3)
=−6x+18
Answer:
Area of the figure = 36 in²
Step-by-step explanation:
Area of the given composite figure = Area of the rectangle ABCE - Area of triangle CDE
Area of rectangle ABCE = Length × Width
= AB × AC
= 6 × 8
= 48 in²
Area of triangle CDE = ![\frac{1}{2}(\text{Base})\times (\text{Height})](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%28%5Ctext%7BBase%7D%29%5Ctimes%20%28%5Ctext%7BHeight%7D%29)
= ![\frac{1}{2}(6)(4)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%286%29%284%29)
= 12 in²
Now area of the composite figure = 48 - 12
= 36 square inch